New clues to the development of the oasis of Dadan. Results from a test excavation at Tall al-Sālimīyyah (al-ʿUlā, Saudi Arabia) - Rohmer, Jerome; Lesguer, Fabien; Bouchaud, Charlène; Purdue, Louise; Alsuhaibani, Abdulrahman; Tourtet, Francelin; Monchot, Hervé; Dabrowski, Vladimir; Decaix, Alexia; Desormeau, Xavier; Alkontar, Rozan Alkhatib; Reiller, Hugo (Proceedings of the Seminar for Arabian Studies, 2023)
This article presents the results of a test excavation conducted by the team of the Dadan Archaeological Project (CNRS/RCU/AFALULA) in October/November 2019 at a peripheral site of ancient Dadan, in the al-ʿUlā valley (north-west Arabia). The excavation data were processed jointly with the ECOSeed archaeobotanical project and the ArcAgr-AU geo-archaeological project. This multidisciplinary approach provides critical new insights into the development of one of the major ancient north-west Arabian oases. The excavations revealed the earliest safely dated archaeological remains in the oasis, associated to the earliest evidence of local date palm cultivation, in the 12th-11th centuries BCE. The results also allow for a reassessment of the earlier archaeological evidence, suggesting a peak in the development of the oasis in the 8th-5th centuries BCE, at the time of the first North-Arabian kingdoms and the rise of long-distance aromatics trade.